Level of Interpersonal Relationship among the Women Student-Teachers in Iraq - Nithyanantham, Vinnaras (International Journal of Psychosocial Rehabilitation, 2020)
The student-teachers are keystones that formulate the holistic development of children. It molds the physical, emotional, intellectual, and social development among students. They must be adopting this interpersonal relationship better than others because they will be working in school with different types of socialized children. Teaching is a profession that demands human relations. To teach effectively, a teacher needs a good interpersonal relationship. This training must be given to all the student-teachers so the level of interpersonal relationship among them can be studied. The investigator had employed the descriptive method using a survey as a technique to study the interpersonal relationships among student teachers. The population of the study consisted of students from the College of Education and Languages, Lebanese French University, Erbil, Kurdistan, Iraq. The investigator had randomly selected 187 student teachers from the College of Education and Languages. The sample consists of 87 women from the General Education Department and 100 women from the English Language Department student teachers. The findings of the present study project that the General Education Department and English Language Department women student-teachers of Lebanese French University do not show any difference in their interpersonal relationships. From the present study revealed that the General Education Department Women Student-teachers of Lebanese French University have better Interpersonal relationship than the English Language Department Women Student-teachers of Lebanese French University